English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please show your work..

2006-10-29 14:53:00 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

First, we integrate by parts:
u=√(1+x^2), v=x, du=x/√(1+x²) dx, dv=dx
∫√(1+x²) dx = x √(1+x²) - ∫x²/√(1+x²) dx
Rewriting the integral on the right:
∫√(1+x²) dx = x √(1+x²) - (∫(x²+1)/√(1+x²) dx - ∫1/√(x²+1) dx)
Simplifying:
∫√(1+x²) dx = x √(1+x²) - ∫√(x²+1) dx + ∫1/√(x²+1) dx
2∫√(1+x²) dx = x √(1+x²) + ∫1/√(x²+1) dx
2∫√(1+x²) dx = x √(1+x²) + ∫1/√(1-(ix)²) dx
Let sin u=ix, cos u du=i dx
2∫√(1+x²) dx = x √(1+x²) - ∫i/√(1-sin² u) cos u du
2∫√(1+x²) dx = x √(1+x²) - ∫i cos u/√(cos² u) du
2∫√(1+x²) dx = x √(1+x²) - iu + C
2∫√(1+x²) dx = x √(1+x²) - i arcsin (ix) + C
∫√(1+x²) dx = (x √(1+x²) - i arcsin (ix))/2 + C

At this point we are technically done, but let's see if we can remove those complex numbers. Let u=arcsin (ix). Then:

sin u = ix
-i sin u = x
-i sin (i(-iu))=x
sinh (-iu)=x (using the identity sinh x=-i sin (ix))
-iu = arcsinh x
So:
-i arcsin (ix)=arcsinh (x)
And:

∫√(1+x²) dx = (x √(1+x²) + arcsinh x)/2 + C

2006-10-29 15:31:53 · answer #1 · answered by Pascal 7 · 0 0

Make the following substitution.

Let u=tan(x). Use the fact that tan^2(x)+1=sec^2(x). And then from here on you should be able to do it.

2006-10-29 22:59:56 · answer #2 · answered by The Prince 6 · 0 0

... and finally, verify using Wolfram Integrator

2006-10-30 17:54:58 · answer #3 · answered by p_ne_np 3 · 0 0

fedest.com, questions and answers